2020
DOI: 10.1111/jomf.12700
|View full text |Cite
|
Sign up to set email alerts
|

Stepfamily Effects on Early Home‐Leaving: The Role of Conflict and Closeness

Abstract: Objective This study examined the role of stepfamily experiences on early home‐leaving with detailed measures for stepfamily experiences that capture levels of closeness and conflict, and with a detailed measure for home‐leaving that captures pathways out of the home. Background Young adults raised in stepfamilies leave home and form unions earlier than young adults raised in single‐parent families. Little is known about the reasons for this difference. This study examined two potential explanations—conflict a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…For example, Steinbach and Hank (2018) showed that adult full siblings are emotionally closer, but simultaneously have more conflicts. van den Berg et al (2021) found that children living in stepfamilies are more likely to experience trajectories such as early home leaving and early union formation, in case they have a distant or conflicted stepchild-stepparent relationship. Future research could enrich our insights in the extent to which and how full, half, or nonbiological siblings show comparability in terms of sibling influences.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Steinbach and Hank (2018) showed that adult full siblings are emotionally closer, but simultaneously have more conflicts. van den Berg et al (2021) found that children living in stepfamilies are more likely to experience trajectories such as early home leaving and early union formation, in case they have a distant or conflicted stepchild-stepparent relationship. Future research could enrich our insights in the extent to which and how full, half, or nonbiological siblings show comparability in terms of sibling influences.…”
Section: Discussionmentioning
confidence: 99%
“…However, while halfand step-siblings are emotionally less close than full-siblings, they also report less sibling conflict and aggression (Sanner et al, 2018;Steinbach & Hank, 2018). Additionally, children living in stepfamilies are more likely to experience trajectories such as early home leaving and early union formation, in case they have a distant or conflicted stepchild-stepparent relationship (van den Berg et al, 2021). Given that modern families, including their sibling composition, are increasingly complex (Sanner et al, 2018), it is highly important to further investigate the potential differences in sibling influence between full-siblings and step-/halfsiblings, taking into account their relationship closeness and length of co-residence.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%